Maternal profiles and outcome of Placenta Accreta Spectrum (PAS) in a retrospective cohort study in Dr. Saiful Anwar General Hospital, Malang, Indonesia - Rahardjo, Bambang; Pratama, Harry Dwi; Purbandari, Rosalia; Alim, Fathi Nabila (Universitas Airlangga, 2025)
HIGHLIGHTS This study compared maternal characteristics and outcomes between PAS and non-PAS patients, including analysis using the Placenta Accreta Index. PAS is associated with significantly higher intraoperative blood loss and postoperative ICU admission rates. Findings underscored the importance of early identification and PAI-based risk stratification to optimize surgical planning and maternal outcomes. ABSTRACT Objective: This study aimed to investigate maternal risk factors associated with PAS among patients at Dr. Saiful Anwar Regional General Hospital in Malang, Indonesia. Materials and Methods: This retrospective cohort study was conducted at Dr. Saiful Anwar General Hospital, Malang, analyzing medical records of patients diagnosed with Placenta Accreta Spectrum (PAS) from January 2023 to August 2024. Patients were categorized into PAS and non-PAS groups, with further classification of PAS patients based on their Placenta Accreta Index (PAI) score (<5 and ≥5) to compare clinical outcomes. A total of 47 eligible patients were included based on gestational age ≥28 weeks, clinical suspicion of PAS, and histopathological confirmation. Demographic, clinical, intraoperative, and postoperative data were collected and analyzed. Data were analyzed using SPSS 27.0. Ethical approval was obtained from the Dr. Saiful Anwar General Hospital Ethics Committee. Results: Patients with PAI scores ≥5 had higher intraoperative blood loss (3467.50 ± 2520.35 mL) compared to those with PAI scores <5 (2212.50 ± 1055.32 mL, p=0.764). Hysterectomy was the primary surgical approach in both groups (PAI <5: 88.88%, PAI <5: 92.75%, p=0.667). Bladder trauma (AAST grade IV) occurred in 100% of patients with PAI <5, whereas bladder infiltration was observed only in the PAI ≥5 group (p=0.117). NICU admission was more frequent in the PAI ≥5 group (31.25% vs. 0%, p=0.061). ICU admission was required in all PAI <5 patients (100%) and 75% of PAI <5 patients (p=0.102). No statistically significant associations were found. Conclusion: Higher PAI score may indicate a more complex clinical course, further research with larger sample sizes is necessary to validate its predictive value.